Assessing the impact of casino gambling on crime in Mississippi - Giacopassi, David (American journal of criminal justice, 1994)
The introduction of legalized gambling into a community has generated a great deal of hubris regarding concomitant criminality. While Las Vegas has long been synonymous with organized crime, the recent focus has been on the connection between traditional crime and legalized gambling. The conventional wisdom among opponents of this new source of revenue is that casinos attract many undesirables to the community, thereby increasing crime and social disorganization. Routine activities theory would suggest that with increased numbers of tourists, more opportunities for crime will exist. To test this proposition, the frequency of crime before and after the introduction of legalized gambling in Biloxi, Mississippi was examined. Larcey-theft and motor vehicle theft were the only categories of crime to show statistically significant change. Robbery and aggravated assault increased, while murder and rape declined, although the change was not statistically significant for any category of violent crime.